The Influence of Group Investigation and Problem-Based Learning Models on Students' Critical Thinking Skills and Learning Motivation in Biology Learning - Margaretha Apriana Wanda; Muh. Amir Masruhim; Evie Palenewan; Daniel; Taufan Purwokusumaning Daru; Elsje Theodora Maasawet (Postgraduate, University of Mataram, 2026)
This study aimed to analyze the effects of the Group Investigation (GI) and Problem-Based Learning (PBL) models on students’ critical thinking skills and learning motivation in biology learning. A quantitative approach with a quasi-experimental design was employed, involving two experimental classes and one control class at SMA Negeri 1 Muara Wahau. The first experimental class implemented the PBL model, the second applied the GI model, while the control class received conventional instruction. Data on students’ critical thinking skills and learning motivation were collected using achievement tests and questionnaires and were analyzed using two-way ANOVA followed by the Least Significant Difference (LSD) post hoc test. The results revealed that the learning model had a significant effect on both critical thinking skills and learning motivation (p < 0.05). Students taught using the PBL model demonstrated the highest improvement in critical thinking skills and learning motivation, followed by those taught using the GI model, while the conventional learning group showed the lowest outcomes. These results indicate that student-centered learning models encourage active engagement, problem-solving, and collaborative learning, which contribute to enhanced cognitive and motivational outcomes in biology learning. In conclusion, both PBL and GI models positively influence students’ critical thinking skills and learning motivation; however, the PBL model is the most effective. Therefore, the implementation of problem-oriented and collaborative learning models is recommended to improve the quality of biology learning processes and outcomes.